Necessity and Opportunity Entrepreneurs and their Duration in Self-employment: Evidence from German Micro Data - Jörn H. Block; Philipp G. Sandner (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
Using data from the German Socio-Economic Panel Study (GSOEP), we analyze whether necessity entrepreneurs differ from opportunity entrepreneurs in terms of self-employment duration. Using univariate statistics, we find that opportunity entrepreneurs remain in self-employment longer than necessity entrepreneurs. However, after controlling for the entrepreneurs' education in the professional area where they start their venture, this effect is no longer significant. We therefore conclude that the difference observed is not an original effect but rather is due to selection. We then go on to discuss the implications of our findings for entrepreneurship-policy making, and give suggestions to improve governmental start-up programs.
urn:nbn:de:bvb:19-epub-2082-6
Keywords: J23; J24; M13; C41; 650; Self-employment; Firm survival; Necessity entrepreneurs; Opportunity entrepre-neurs; Hazard rates; GSOEP